"Development initiatives in India/ edited by V.Narayana Reddy, D.Sunder Raj [and] M.Romesh Singh" - "Reddy, V.Narayana (ed.)" (New Delhi, 2008)
The Development Architects in India have experimented with many socio economic development programmes under the trickle down approach. The book containing the following topics; Agriculture Development, Rural Development, Women Development and Social Development.
Keywords: Agricultural development-India